Antioxidant Status Of Goat Liver Slices Treated With Methanolic Leaf Extract Of Nyctanthes Arbor-Tristis Exposed To Oxidative Stress - SUMATHI,S.; SOWMINI,C.M.; DHARANI,B.; SIVAPRABHA.J.; PADMA, P.R. (International Journal of Pharma and Bio Sciences, 2011)
A number of natural compounds found in plants display potential role as chemo preventive agents. Hence plant products have been used recently in treatment of several diseases. The plant selected for the present study is Nyctanthes arbor-tristis (Family: Oleaceae) commonly known as Pavazhamalli. Its leaves are traditionally used to treat fever, rheumatism, liver disorders and as expectorant. In the present study we estimated the antioxidant status of goat liver slices (in vitro model) that were exposed to oxidative stress induced by hydrogen peroxide and co-treated with methanolic leaf extract of Nyctanthes arbor-tristis. The enzymic antioxidants like Catalase, Glutathione Peroxidase, Superoxide Dismutase and Glutathione-S-Transferase and the non-enzymic antioxidants like Vitamin C and reduced glutathione were analyzed in the presence and absence of hydrogen peroxide. Treatment with hydrogen peroxide decreased the antioxidant status of goat liver slices and co-treatment with the extract improved the antioxidant status of liver slices